Ex Utero Intrapartum Treatment for Fetal Oropharyngeal Cyst - Allen W. Ayres; Suzanne K. Pugh (Obstetrics and Gynecology International)
Background. A prenatally diagnosed fetal anomaly that could compromise the fetal airway at delivery can be managed safely with the ex utero intrapartum treatment (EXIT) procedure. Case. A 26-year-old healthy primigravida was diagnosed during her midtrimester anatomic ultrasound survey with a fetal oropharyngeal cystic structure located at the base of the tongue. The neonatal airway was successfully secured intrapartum using the EXIT procedure. Conclusion. Maintenance of fetoplacental circulation until the fetal airway is secured has been described for a multitude of fetal anomalies including cystic hygroma and teratoma. The literature also recounts its use for the reversal of tracheal plugging for congenital diaphragmatic hernia. A multidisciplinary approach to the antenatal and intrapartum care is essential for the successful management of these cases.